2014
DOI: 10.1353/hpu.2014.0038
|View full text |Cite
|
Sign up to set email alerts
|

Race and Socioeconomic Differences in Obesity and Depression among Black and Non-Hispanic White Americans

Abstract: Obesity and depression often co-occur; however, the association between these conditions is poorly understood, especially among racial/ethnic minority groups. Using multinomial logistic regression and data from the National Survey of American Life, the relationships between race, ethnicity, and sociodemographic factors to the joint classification of body mass index categories and depression among African Americans, Caribbean Blacks, and non-Hispanic Whites were examined. Differential risk for the combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
(62 reference statements)
4
32
1
Order By: Relevance
“…[38][39][40][41] Previous studies document an association between weight status and emotional disorders, especially depression. 18,20 Of the students endorsing depressive symptoms in the current study, the majority were females (67.7%). The overall rate of depressive symptoms was high in this cohort, 28.4%.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[38][39][40][41] Previous studies document an association between weight status and emotional disorders, especially depression. 18,20 Of the students endorsing depressive symptoms in the current study, the majority were females (67.7%). The overall rate of depressive symptoms was high in this cohort, 28.4%.…”
Section: Discussionmentioning
confidence: 70%
“…[15][16][17] Although the prevalence of co-occurring obesity and psychological disorders vary by race [18][19][20] , depressive symptoms, anxiety, and eating disorders co-occur with obesity. 15,18 Studies assessing the correlation between weight and poor self-concept demonstrated lower self-concept in individuals with higher body weight. 16 Body dissatisfaction and depression differentially affected adolescent girls more than boys.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, though the variation is small, genetic risk factors have been shown to predict obesity in non-Hispanic blacks [32, 33]. There is also evidence showing the association of obesity with low socio-economic status [34, 35]. Low socio-economic status in terms of lower income, lower educational attainment and lower literacy levels [36, 37] are associated with poor health outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, overweight and obesity among female adults have increased from 29.8-38.0% between 1980 and 2013 respectively [32], with a recent study conducted in Zimbabwe [33] con rming these ndings for the time period 2005 to 2015. Differences in experiencing obesity and overweight among socioeconomic subgroups [34] may be linked to IPV in complex ways. For example, prior evidence suggests that abused women may end up suffering from depression [35], and may hence seek consolation in overeating [36].…”
Section: Introductionmentioning
confidence: 99%